Analisis Kualitas Pelayanan E-KTP Menggunakan Metode Customer Satisfaction Index, Metode Service Quality, dan Importance Performance Analysis - Siti Noor Hidayati; Aris Puji Prasetyo (Jurnal Maksipreneur, 2015)
This study attempts to analyzed levels of customer satisfaction on the quality of service and anything in the dimensions attributes the quality of services have to be prioritized to repairing in order to increase customer satisfaction. This study uses a Customer Satisfaction Index to measure the overall level of customer satisfaction.To sort the attributes do not satisfy the customer satisfaction levels by measuring the difference in performance levels using Service Quality. Then proceed with the measure by using Importance Performance Analysis to determine the attributes that have not been satisfying the customers.  Results of this study showed that the majority of customers are satisfied with the services provided but not maximum yet. It can be seen from the results of customer satisfaction level testing using Customer Satisfaction Index (CSI) which is equal to 53,7%. Based on testing using the Service Quality attributes improvements sequence starting from the attribute assurance because it has the greatest negative value.On testing using the Importance Performance Analysist (IPA), there are 8 service attributes that go into quadrant I, which means that there are 8 attributes that unsatisfactory customers and the service is not maximum yet.